Causality between financial development, economic growth, and income inequality in EU countries (International Journal of Applied Research in Management and Economics, 2022)
This study investigates the causality between financial development, economic growth, and income inequality using panel data for 23 European Union countries over the period 1987-2017. Various proxies of financial development are chosen to represent the depth, efficiency, and stability of the banking system and stock markets. For the empirical analysis, the study performs the Granger non-causality test in heterogeneous panels. The findings are contradictory and sensitive to the measures of financial development. Most importantly, the results reveal a one-way causality from financial development to economic growth when private credit, stock market capitalization, net margin interest rate, and Z-score are chosen as financial development indicators. In addition, a two-way causality exists between bank assets, liquid liabilities, non-performing loans, and economic growth, and a one-way causality from economic growth to value traded and turnover ratio. However, the results show no causality between stock price volatility and economic growth. The results indicate a one-way causality running from income inequality to economic growth. Finally, a one-way causality runs from income inequality to financial development for most measures of financial development except for a one-way causality running from private credit to income inequality, a two-way causality between bank assets and inequality, and an absence of causality between income inequality and turnover ratio, Z-score and stock price volatility.